P79 FIRST GENERATION BIORESORBABLE VASCULAR SCAFFOLD VS NEXT GENERATION BIORESORBABLE VASCULAR SCAFFOLD: SINGLE CENTER, LONG–TERM FOLLOW UP EXPERIENCE. (18th May 2022) - Albani, S; Pisano, F; Bernardi, A; Amato, G; Bonino, C; Biava, L; Contu, L; Pelloni, E; Scacciatella, P
Abstract: Background: Previous randomized controlled trials demonstrated a higher rate of stent thrombosis with first generation (Absorb; Abbott Vascular, USA) bioresorbable vascular scaffold (BVS) implantation as compared with second–generation drug–eluting stent. Currently, with limited indications, others next generation BVS (NGB) are available (Magmaris; Biotronik AG, Switzerland and DESolve; Elixir Medical Corporation, USA). Real world long–term outcomes of such devices are limited. Methods and Results: In our center from 27/09/2012 to 28/08/2018 in a cohort of 277 patients, a total of 259 BVS and 191 NGB (120 Magmaris and 71 DESolve) devices were implanted. The primary efficacy endpoint was a combined end point of target–lesion revascularization (TLR) and target lesion myocardial infarction (TLMI) the primary safety endpoint was scaffold thrombosis (ScT). At a median follow–up, of 83 months (interquartile range–IQR, 61–91 months) for BVS, and 48 months (IQR, 41–53.5 months) and 64.5 months (IQR, 58.5–69 months) for Magmaris and DESolve respectively, TLR/TLMI occurred in 17 patients (10.5%) in the BVS group and 4 patients (3.5%) in the NGB group (p value= 0.03), ScT occurred in 5 patient (3.1%) and 1 patient (0.9%), p–value=0.23, respectively. Median time of ScT occurrence in the BVS group was 12.5 months (IQR 9.75–16.75), ScT in the NGB group occurred after patient's suspension of dual antiplatelet therapy 3 months later from the implantation date. Conclusion: In a single center real world setting, the use of NGB appear safer compared to BVS at long–term follow–up.